The Influence of Leadership Behavior and Job Satisfaction on the Work Performance of Inpatient Nurses at Harapan Mulia Cibarusah Cikarang Hospital - Saputra, Rachmat Belgi; Aziz, Abdul; Rinaldi, Enrico Adhitya (IJBLE Scientific Publications Community Inc., 2025)
Nursing services delivered to patients are reflected in the work performance of nurses. Achieving optimal work performance remains a challenge, as several factors influence it, including leadership behavior and job satisfaction. Addressing these challenges requires appropriate interventions, particularly in strengthening leadership behavior and enhancing job satisfaction to improve nurses’ performance. The aim of this study was to examine the influence of leadership behavior and job satisfaction on the work performance of inpatient nurses. This study employed a non-experimental, cross-sectional analytic design. Logistic regression analysis was conducted using SPSS version 24.0 to assess the influence of the independent variables (leadership behavior and job satisfaction) on the dependent variable (work performance). Data were collected through questionnaires administered to 39 inpatient nurses at Harapan Mulia Cibarusah Cikarang Hospital. The findings revealed a significant effect of leadership behavior on work performance with a p-value of 0.009 (p < 0.05) and an Odds Ratio (OR) of 12.818, indicating that nurses experiencing poor leadership behavior were 12.818 times more likely to have low work performance compared to those under effective leadership. Job satisfaction also had a significant effect on work performance, with a p-value of 0.048 (p < 0.05) and an OR of 7.051, meaning that nurses with low job satisfaction were 7.051 times more likely to have poor work performance compared to those who were satisfied. The R-square value obtained was 0.607, signifying that leadership behavior and job satisfaction collectively explained 60.7% of the variance in work performance, while the remaining 39.3% was influenced by other unexamined factors. Among the two variables studied, leadership behavior exerted the strongest influence on nurses’ work performance, as indicated by its higher OR compared to job satisfaction. It is recommended that hospital management strengthen leadership practices among ward heads and consistently attend to the job satisfaction of inpatient nurses, thereby fostering constructive improvements in work performance.